Establishment of an optimized guinea pig model of cisplatin-induced ototoxicity - Ahmadi, Navid; Saidov, Nodir; Gausterer, Julia Clara; Kramer, Anne-Margarethe; Honeder, Clemens; Arnoldner, Christoph (Frontiers in Veterinary Science, 2023)
Background Cisplatin is among the most effective antineoplastic agents and has revolutionized the treatment of many cancer diseases. However, one of its serious side effects is a progressive and irreversible hearing loss, occurring in both adults and children. For the development of otoprotective therapies that prevent this side effect, cisplatin-induced hearing loss animal models are indispensable. Due to the high toxicity of cisplatin, the establishment of such animal models is a difficult and time-consuming task. Here we introduce the detailed protocol of a sophisticated guinea pig model with a sufficient and permanent hearing loss induced by cisplatin. This manuscript is intended to provide guidance in the development of future cisplatin guinea pig models which may reduce the mortality rate of the animals and help to gain more reproducible results. Methods Pigmented and unpigmented guineapigs were treated with an intravenous single application of 8mg/kg cisplatin under general anesthesia. An extensive and long-term intensive care protocol consisting of scheduled application of fluids, antiemetics, analgesics, glucose and supportive feeding among others, was used to ensure wellbeing of the animals. Hearing tests were performed prior to and 5 days after cisplatin application. Animals were then euthanized. Results The ABR audiometry 5 days after cisplatin application revealed a hearing threshold ranging from 70dB to 90dB in the frequencies from 1kHz to 32kHz respectively. All animals presented a good health condition despite the treatment with cisplatin. Discussion The introduced care protocol in this manuscript is intended to serve as a guidance for the establishment of a stable guinea pig model for short- and long-term investigation regarding the inner ear and its protection in the frame work of cisplatin-induced damage.